2016
DOI: 10.1186/s13049-016-0302-8
|View full text |Cite
|
Sign up to set email alerts
|

Ambulance helicopter contribution to search and rescue in North Norway

Abstract: BackgroundSearch and rescue (SAR) operations constitute a significant proportion of Norwegian ambulance helicopter missions, and they may limit the service’s capacity for medical operations. We compared the relative contribution of the different helicopter resources using a common definition of SAR-operation in order to investigate how the SAR workload had changed over the last years.MethodsWe searched the mission databases at the relevant SAR and helicopter emergency medical service (HEMS) bases and the Joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…More men (39) than women (21) were evacuated, and the patients were engaged in a variety of activities at the time of the injury or falling ill (Table 5). The median (quartiles) response time was 47 (33-62) min, including a median (quartiles) take-off time of 9 (5)(6)(7)(8)(9)(10)(11)(12)(13) 14; autumn [September−November]: 13). More than one-third of the incidents occurred during the weekend, with the most on Saturdays (n¼14).…”
Section: Characteristics Of the Patients And The Incidentsmentioning
confidence: 99%
“…More men (39) than women (21) were evacuated, and the patients were engaged in a variety of activities at the time of the injury or falling ill (Table 5). The median (quartiles) response time was 47 (33-62) min, including a median (quartiles) take-off time of 9 (5)(6)(7)(8)(9)(10)(11)(12)(13) 14; autumn [September−November]: 13). More than one-third of the incidents occurred during the weekend, with the most on Saturdays (n¼14).…”
Section: Characteristics Of the Patients And The Incidentsmentioning
confidence: 99%
“…Poor weather conditions have been reported to frequently cause denied or cancelled HEMS and search and rescue (SAR) missions [14, 17]. Studies have reported that 5.1–9.7% of all requested HEMS missions are denied or cancelled yearly due to poor weather conditions with the rotor wing aircraft [1, 2].…”
Section: Discussionmentioning
confidence: 99%
“…The decision regarding the method of insertion and extraction of persons during rescue missions is solely in the hands of the helicopter's pilot, who has to evaluate all influencing factors so as to minimize the risk to flight safety. Among the fundamental evaluated factors are wind speed and direction, turbulence, altitude, air temperature, location (water/land), position of the persons (free terrain/up a tree/on a roof/in a rock wall), terrain features (plain/mountainous terrain/mountain-climbing terrain), forestation and its height, the number of persons requiring transport and more [8]. The simplest and most secure method is always preferred.…”
Section: Discussionmentioning
confidence: 99%
“…If necessary extraction one or two people, it is better to use the on-board hoist. Based on the abovementioned reasons it is also true that in coastal countries and in rescue operations taking place more than 10 km from the coast, the on-board hoist is the only viable option of extracting persons from the sea [8].…”
Section: 22mentioning
confidence: 99%